Siglec15 is a prognostic indicator and a potential tumor-related macrophage regulator that is involved in the suppressive immunomicroenvironment in gliomas - Wang, Jinchao; Xu, Linzong; Ding, Qian; Li, Xiaoru; Wang, Kai; Xu, Shangchen; Liu, Bin (Frontiers in Immunology, 2023)
Background: Siglec15 is rising as a promising immunotherapeutic target in bladder, breast, gastric, and pancreatic cancers. The aim of the present study is to explore the prognostic value and immunotherapeutic possibilities of Siglec15 in gliomas using bioinformatics and clinicopathological methods. Methods: The bioinformatics approach was used to examine Siglec15 mRNA expression in gliomas based on TCGA, CGGA, and GEO datasets. Then, the predictive value of Siglec15 expression on progression-free survival time (PFST) and overall survival time (OST) in glioma patients was comprehensively described..The TCGA database was screened for differentially expressed genes (DEGs) between the high and low Siglec15 expression groups, and enrichment analysis of the DEGs was performed. The Siglec15 protein expression and its prognostic impact in 92 glioma samples were explored using immunohistochemistry Next, the relationships between Siglec15 expression and infiltrating immune cells, immune regulators and multiple immune checkpoints were analysed. Results: Bioinformatics analyses showed that high Siglec15 levels predicted poor clinical prognosis and adverse recurrence time in glioma patients. In the immunohistochemical study serving as a validation set, Siglec15 protein overexpression was found in 33.3% (10/30) of WHO grade II, 56% (14/25) of WHO grade III, and 70.3% (26/37) of WHO grade IV gliomas respectively. Siglec15 protein overexpression was also found to be an independent prognostic indicator detrimental to the PFST and OST of glioma patients. Enrichment analysis showed that the DEGs were mainly involved in pathways associated with immune function, including leukocyte transendothelial migration, focal adhesion, ECM receptor interaction, and T-cell receptor signaling pathways. In addition, high Siglec15 expression was related to M2 tumor-associated macrophages (TAMs), N2 tumor-infiltrating neutrophils, suppressive tumor immune microenvironment, and multiple immune checkpoint molecules. Immunofluorescence analysis confirmed the colocalization of Siglec15 and CD163 on TAMs. Conclusion: Siglec15 overexpression is common in gliomas and predicts an adverse recurrence time and overall survival time. Siglec15 is a potential target for immunotherapy and a potential TAMs regulator that is involved in the suppressed immunomicroenvironment in gliomas.